Identification of potential interferents of methylmalonic acid: a previously unrecognized pitfall in clinical diagnostics and newborn screening - Monostori, Péter; Godejohann, Markus; Janda, Joachim; Galla, Zsolt; Rácz, Gábor; Klinke, Glynis; Szatmári, Ildikó; Zsidegh, Petra; Kohlmüller, Dirk; Kölker, Stefan; Hoffmann, Georg F.; Gramer, Gwendolyn; et al. (Clinical biochemistry, 2023)
Determination of methylmalonic acid (MMA) from dried blood spots (DBS) is commonly performed in clinical diagnostics and newborn screening for propionic acidemia (PA) and methylmalonic acidemia. Isobaric compounds of MMA having the same mass can affect diagnostic reliability and quantitative results, which represents a previously unrecognized pitfall in clinical assays for MMA. We set out to identify interfering substances of MMA in DBS, serum and urine samples from confirmed patients with PA and methylmalonic acidemia.